Exploring factors influencing chiropractors’ adherence to radiographic guidelines for low back pain using the Theoretical Domains Framework - Daphne To; Amanda Hall; André Bussières; Simon D. French; Rebecca Lawrence; Andrea Pike; Andrea M. Patey; Debbie Brake-Patten; Lino O’Keefe; Barbara Elliott; Diana De Carvalho (Chiropractic & Manual Therapies, 2022)
Abstract Background The inappropriate use of lumbar spine imaging remains common in primary care despite recommendations from evidence-based clinical practice guidelines to avoid imaging in the absence of red flags. This study aimed to explore factors influencing ordering behaviours and adherence to radiographic guidelines for low back pain (LBP) in chiropractors in Newfoundland and Labrador (NL), Canada. Methods We conducted two focus groups in December 2018 with chiropractors in different regions of NL (eastern, n = 8; western, n = 4). An interview guide based on the Theoretical Domains Framework (TDF) served to identify perceived barriers to, and enablers of, target behaviours of guideline adherence and managing LBP without X-rays. We conducted thematic analysis of chiropractors’ statements into relevant theoretical domains, followed by grouping of similar statements into specific beliefs. Domains key to changing radiographic guideline adherence, LBP imaging behaviours, and/or informing intervention design were identified by noting conflicting beliefs and their reported influence on the target behaviours. Results Six of the 14 TDF domains were perceived to be important for adherence to radiographic guidelines and managing non-specific LBP without imaging. Participating chiropractors reported varying levels of knowledge and awareness of guidelines for LBP imaging (Knowledge). Many chiropractors based their decision for imaging on clinical presentation, but some relied on “gut feeling” (Memory, attention, and decision processes). While chiropractors thought it was their role to manage LBP without imaging, others believed ordering imaging was the responsibility of other healthcare providers (Social/professional role and identity). Contrasting views were found regarding the negative consequences of imaging or not imaging LBP patients (Beliefs about consequences). Communication was identified as a skill required to manage LBP without imaging (Skills) and a strategy to enable appropriate imaging ordering behaviours (Behavioural regulation). Chiropractors suggested that access to patients’ previous imaging and a system that facilitated better interprofessional communication would likely improve their LBP imaging behaviours (Behavioural regulation). Conclusion We identified potential influences, in six theoretical domains, on participating chiropractors’ LBP imaging behaviours and adherence to radiographic guidelines. These beliefs may be targets for theory-informed behaviour change interventions aimed at improving these target behaviours for chiropractors in NL.